Implementation of the Revised Technology and Livelihood Education (TLE) Curriculum in the Schools Division of Tabaco City - Berces, Judy Ann (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the implementation of the revised Technology and Livelihood Education (TLE) curriculum in the public secondary schools of the Schools Division of Tabaco City. Anchored on Transformational Leadership Theory, Instructional Leadership Theory, Systems Theory, Distributed Leadership Theory, the Integrated Curriculum Implementation Theory, and the Input–Process–Output–Outcome framework, the study assessed curriculum implementation in terms of teacher expertise, relevant trainings, learning resources, monitoring and evaluation, and feedback. A mixed-methods research design was used. Quantitative data were gathered through a structured researcher-made questionnaire, while qualitative data were obtained through semi-structured interviews. The respondents consisted of 45 TLE teachers and 11 school principals selected through total enumeration. Data were analyzed using frequency counts, percentages, weighted mean, and thematic analysis. Findings showed that teacher expertise was highly implemented, monitoring and evaluation were also highly implemented, feedback mechanisms were implemented, relevant trainings were implemented but with teacher-perceived limitations, and learning resources were fairly implemented. The major strategies identified were collaborative planning, resource prioritization, mentoring, use of monitoring data, and external partnerships. The main challenges included limited budget, insufficient hands-on training, inadequate learning resources, large class sizes, limited instructional time, weak partnerships, and coordination gaps. The study concluded that while the revised TLE curriculum was generally implemented, improvement is needed in training, resources, feedback systems, and stakeholder collaboration. The study supports SDG 4, SDG 8, SDG 9, and SDG 17 by promoting quality education, employability, technical skills development, and partnerships. Its sustainability impact lies in strengthening educational, socio-economic, institutional, and workforce-readiness outcomes through improved TLE curriculum implementation.
Keywords: Collaborative Planning; Curriculum Implementation; Learning Resources; Monitoring and Evaluation; School Leadership; Teacher Expertise; Technical-Vocational Education; Technology and Livelihood Education; Training Development